Sans sépulture : modalités et enjeux de la privation de funérailles de la préhistoire à nos jours - Schmitt, Aurore, (Archaeopress Archaeology, 2023)
This volume gathers contributions from archaeologists, anthropologists and historians to present a rich interdisciplinary and diachronic reflection on the diversity of motivations that lead to the intentional deprivation of funerals.